Embryology of the spider crabs Leurocyclus tuberculosus (H. Milne-Edwards & Lucas 1842) and Libinia spinosa (H. Milne-Edwards 1834) (Brachyura, Majoidea) - Gonzalez Pisani, Ximena (2013)
The embryonic development of the spider crabs Leurocyclus tuberculosus and Libinia spinosa was described based on laboratory reared specimens. Living embryos were removed from female every 48 h and external morphometric traits, dimensions and development time were registered. Total development was divided into five periods based on: I) the cleavage, II) the embryonic primordium, III) the optic lobes, IV) the pigmentation in the optic lobes and V) the chromatophores. Different characteristics like spines, setae, telson morphology and processes, make both species distinguishable from the period III until hatching. Egg volume was greater in Leurocyclus tuberculosus than in Libinia spinosa. The duration of each period was not similar during development; while in L. tuberculosus the period II (morphogenesis) is the longest, in L. spinosa, the period IV (pigmentation) is the longest. Complete embryonic development at 14°C lasted 36 days in Leurocyclus tuberculosus and 57 days in Libinia spinosa. The knowledge about the embryonic development is essential for studies on reproduction and fundamental ecology of marine bottom invertebrates. It provides a useful tool to determine the time elapsed since spawning and the time remaining before hatching in live eggs, in ecological and comparative studies.